ҲАРБИЙ ХИЗМАТЧИЛАРДАГИ КАСБИЙ ЗЎРИҚИШЛАРНИНГ ПСИХОЛОГИК ТАХЛИЛИ ВА УНИНГ НАЗАРИЙ ҲАМДА АМАЛИЙ АҲАМИЯТИ - Шерматов, Ф.Т. (SCIENCE and SOCIETY, 2021)
In this scientific article, the theoretical and practical aspects of the research conducted on the basis of the author’s service experience are studied in detail, psychological analysis of occupational stress in military personnel in the process of training and educational combat training was studied on the basis of comparative examples and analyzed on the basis of the student’s t-criterion.